2016
DOI: 10.1007/s10509-016-2686-3
|View full text |Cite
|
Sign up to set email alerts
|

Radio planetary nebulae in the Small Magellanic Cloud

Abstract: We present ten new radio continuum (RC) detections at catalogued planetary nebula (PN) positions in the Small Magellanic Cloud (SMC): SMP S6, LIN 41, LIN 142, SMP S13, SMP S14, SMP S16, J 18, SMP S18, SMP S19 and SMP S22. Additionally, six SMC radio PNe previously detected, LIN 45, SMP S11, SMP S17, LIN 321, LIN 339 and SMP S24 are also investigated (re-observed) here making up a population of 16 radio detections of catalogued PNe in the SMC. These 16 radio detections represent ∼15 % of the total catalogued PN… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
(85 reference statements)
0
8
1
Order By: Relevance
“…We used the combined sample of 37 radio PNe from the LMC and the SMC (Leverenz et al 2016) with available re- Table 6. Parameters of the simulated samples and results of the sensitivity simulations for the LMC sample and the combined sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used the combined sample of 37 radio PNe from the LMC and the SMC (Leverenz et al 2016) with available re- Table 6. Parameters of the simulated samples and results of the sensitivity simulations for the LMC sample and the combined sample.…”
Section: Discussionmentioning
confidence: 99%
“…6). Additionally we included nine SMC PNe from Leverenz et al (2016): SMP S6, SMP S13, SMP S14, SMP S16, SMP S17, SMP S18, SMP S19, SMP S22, and SMP S24. These SMC PNe were unambiguously determined not to be PN mimics and were also re-scaled to the distance of the LMC.…”
Section: Radio-continuum Properties Of the Detected Pnementioning
confidence: 99%
See 1 more Smart Citation
“…Radio emission from star-forming galaxies originates from two main sources, thermal emission from HII regions and non-thermal emission from Cosmic Ray electrons (CRe) that have been accelerated in SNR shock fronts. It is unlikely that any detections are related to X-ray binaries or Planetary Nebulae (Fender & Hendry 2000;Leverenz et al 2016) as at the distance of IC 10, these sources would have flux densties of order 1 µJy. Very long baseline interferometers, such as e-MERLIN, effectively resolve out nearly all extended emis-sion within observed galaxies, essentially highlighting compact star-forming products and contaminating background sources.…”
Section: Resultsmentioning
confidence: 99%
“…To date, some 85 SNRs in the MCs have been identified, with a further 20 candidates awaiting confirmation (Maggi et al 2016;Bozzetto et al 2017). Similarly, over 50 PNe (Filipović et al 2009;Bojičić et al 2010;Leverenz et al 2016Leverenz et al , 2017 and hundreds of H ii regions and YSOs have been identified (see for example Oliveira et al 2013). Over 8500 radio sources have also been E-mail: tana.joseph@manchester.ac.uk (TDJ) detected in the region of the Clouds -mainly AGN, radio galaxies and quasars (Wong et al 2012b;Collier 2016, Grieve et al in prep.).…”
Section: Introductionmentioning
confidence: 97%